Megarthrus of China. Part 1. Description of a new species resembling M. antennalis Cameron, 1941 (Coleoptera: Staphylinidae: Proteininae) - Liu, Zhiping; Cuccodoro, Giulio (Zootaxa, 2020)
Megarthrus chujiao Liu and Cuccodoro sp. nov., from Sichuan and Yunnan provinces in China is described and illustrated. It is the third record of the genus in the Hengduan Mountains, and the first endemic Megarthrus species from this temperate biodiversity hotspot. Megarthrus chujiao strongly resembles M. antennalis Cameron, 1941, from Nepal and North India, with which they form a new complex of species—the M. antennalis-complex within the predominantly Holactic and African M. depressus-supergroup of species.